Transboundary river water quality assessment: a case study of Kabul River Basin, Pakistan - Hussain, Kashif; Iqbal, Muhammad Shahid; Munir, Sarfraz; Bilal, H. (Springer, 2025)
In developing countries, microbial contamination of freshwater resources is a significant public health concern. The concentrations of Escherichia coli (E. coli) and influencing factors in the Kabul River Basin (KRB), Pakistan, were evaluated in this research, using the Soil and Water Assessment Tool (SWAT) model under various climate change scenarios. Streamflow (R2 = 0.66–0.71, NSE = 0.62–0.68) and E. coli (R2 = 0.70, NSE = 0.69) concentrations were utilized to calibrate and validate the model. Higher values of E. coli concentrations (3.55 to 5.20 log cfu/100 ml) were observed during flood events. In 2050, according to Scenario-P1, point sources (human settlements) accounted for 19.7% of E. coli concentrations, non-point sources (livestock) for 46.8%, and upstream sources for 33.5%. This data is based on a moderate growth scenario that incorporates enhanced sanitation. In Scenario-P1, the quantity of E. coli decreased by 70% in comparison to the initial value. Additional advancements in sanitation practices and manure treatment (scenarios Aa, Ab, Ac) resulted in significant decreases in E. coli concentrations, reaching as low as 96%. On the contrary, under standard operating conditions (Scenario-P2), where sanitation and effluent treatment were inadequate, the prevalence of E. coli escalated by 158% by 2050 and further escalated by 201% by 2100. E. coli concentrations were influenced by climate change in conjunction with socioeconomic factors. To reduce E. coli concentrations in the KRB, enhanced sanitation, wastewater treatment, and manure management are emphasized in this study. The findings underscore the urgent need for immediate, robust interventions in wastewater treatment and sanitation infrastructure to prevent further public health risks. Without these critical improvements, the future health of the Kabul River Basin’s population will remain under significant threat from escalating waterborne diseases, exacerbated by climate change.